What Are We Talking About When We Say ‘Hope’? Theological Contributions and Challenges for Christianity Today - Susana Vilas Boas (Religions)
The concept of hope has varied in meaning from ancient Greece to the present day. Often understood as an expectation or an illusion, hope seems to greatly determine the way human beings live and think about their existence. It is precisely in this context that the questioning of the Christian faith and particularly eschatology arises. The aim of this article is to analyse the concept of Hope, distinguishing it from concepts such as expectations and hopes, and placing it in the sphere of Christian life and theology. In this context, realities such as immortality, eternity, and death will be explored in order to understand if there is room for a Hope that goes beyond empirical certainty or capricious and illusory desire.